Boar welfare influence the quality of the gametes - Almeida, Thiago Bernardino de (2021)
In commercial pig breeding farms, boars are often exposed to stressful situations, such as individual housing, inadequate ambient temperature, food restriction, lack of social interaction, illness, among other challenges. The consequences stressful situations for the welfare of the breeding boars and possible impacts in semen quality and developmental outcomes of their offspring are largely unknown. Recent research, in rodents, indicated that epigenetic effects in semen are responsible for changes in the metabolism and behavior of the offspring, including for subsequent generations, thus modulating the resilience of the animals and, consequently, their welfare. Small non- coding RNAs population in semen is our study targets because it represents the potential mechanisms to explain developmental outcomes represented as survival, growth, behavioral and physiological modulation, previously reported, from our own research group, in the offspring. This research were carried out in two separate, but complementary, experiments. Our aim was to measure 1) the impact of an endotoxin challenge (n=13) or saline (n=13) in 26 crated boars that were brushed (n=13) or not brushed (n= 13), as a protocol to promote environmental enrichment, and the consequences of the experimental protocol to their behavior and semen characteristics, and the impact of different housing conditions, conventional crates (n=9), pens (n=9) and environmental enriched pen (n=9), on behavioral parameters, stress physiology (n=27) and molecular seminal indicators (n=18) of young breeding boars. We identified that the endotoxin challenge changed the rectal temperature and the salivary cortisol concentration of crated boars and that brushing modulated their behavior and their cortisol response during challenge. In our study, LPS challenge did not change semen features. In the second study, we identified that boars housed in crates performed more abnormal behavior when compared with boars housed in pens or enriched pens. Boar kept in enriched pens showed a significant higher ratio between AM and PM cortisol levels, which are indicators of appropriated HPA axis functioning, than crated boars and boars kept in non-enriched pens. Moreover, boars housed in crates had robust indicators of compromised testis health, higher superficial scrotum temperature, including alterations in sperm motility and sperm agglutination. The study of microRNAs showed significant differences in the abundance of 12 microRNAs out of 266 studied. The microRNAs which showed differences in the abundance on the ejaculate of boars kept in enriched pens could explain the superior markers in semen quality indicators and larger number of piglets born alive, observed in these boars, when compared with boars kept in crates or non-enriched pens. This work is pioneer in investigate the impact of housing conditions of boars in their welfare and performance. Boars kept in crates had testis physiology and health compromised, and for this reason, breeding boars should be kept in pens.